Taking Back Control? Quasi-Experimental Evidence on the Impact of Retirement on Locus of Control - Andrew E. Clark; Rong Zhu (Institute of Labor Economics (IZA), 2023)
We use nationally representative panel data from Australia to consider the impact of retirement on individual locus of control, a socio-emotional skill that has substantial explanatory power for a broad range of life outcomes. We establish causality via cohort-specific eligibility age for the Australian Age Pension. We show that retirement leads to increased internal locus of control. This greater sense of internal control can explain around one-third and one-fifth of the positive effects of retirement on health and subjective well-being, respectively. The impact of retirement on control beliefs varies along the distribution of locus of control, with the positive influence being most pronounced for men with a relatively high sense of internal control and for women with a relatively high sense of external control. Last, we provide evidence that locus of control is much more malleable at retirement than the other socio-emotional skills of the Big-Five personality traits, risk and time preferences, and trust.
Keywords: H55; J24; J26; 330; retirement; locus of control; socio-emotional skills; public pension